Area-level deprivation and geographic factors influencing utilisation of General Practitioner services. (September 2021) - Barlow, Peter; Mohan, Gretta; Nolan, Anne; Lyons, Seán
Abstract: Inequities in access to General Practitioner (GP) services are a key policy concern given the role of GPs as gatekeepers to secondary care services. Geographic or area-level factors, including local deprivation and supply of healthcare providers, are important elements of access. In considering how area-level deprivation relates to GP utilisation, two potentially opposing factors may be important. The supply of healthcare services tends to be lower in areas of higher deprivation. However, poorer health status among individuals in deprived areas suggests greater need for healthcare. To explore the relationship of area-level deprivation to healthcare utilisation, we use data from the Healthy Ireland survey, which provided a sample of 6326 respondents to face-to-face interviews. A u-shaped relationship between GP supply and area-level deprivation is observed in the data. Modelling reveals that residing in more deprived communities has a strong, statistically significant positive association with having seen a GP within the last four weeks, controlling for individual characteristics and GP supply. All else equal, residing in an area ranked in the most deprived quintile increases the odds of a respondent having visited the GP in four weeks by 1.43 (95% Confidence Interval: 1.15–1.78), compared to the least deprived quintile (p-value< 0.001). The findings indicate that the level of deprivation in an area may be relevant to decisions about how to allocate primary care resources. Highlights: GP utilisation is higher amongst those in more deprived areas. GP supply is lower in middle income areas compared to deprived or affluent areas. Differences in GP supply and GP utilisation occur across deprivation quintiles. Other geographic factors are not found to be significant in determining GP utilisation.